Occult tumour cells in peritoneal lavage are a negative prognostic factor in pancreatic cancer - Havlik, Roman; Srovnal, Josef; Klos, Dusan; Benedikova, Andrea; Lovecek, Martin; Ghothim, Mohamed; Cahova, Dana; Neoral, Cestmir; Hajduch, Marian (Biomedical papers of the Medical Faculty of the University Palacky, Olomouc, Czechoslovakia, 2013)
AIMS: The aim of this study was to test the hypothesis that occult tumour cells in peritoneal lavage are a negative prognostic factor in pancreatic adenocarcinoma. METHODS: Real-time RT-PCR analysis of CEA, EGFR and hTERT transcript levels was used to identify occult tumour cells in peritoneal lavage samples from 96 pancreatic cancer patients. RESULTS: We found significant association between CEA expression levels in peritoneal lavage and clinical stage. We also found that EGFR transcript levels were higher in peritoneal lavage samples from patients with high grade tumours than in samples from patients with low grade tumours. Detection of CEA and/or EGFR occult tumour cell markers in the peritoneal lavage was associated with significantly shorter overall survival and increased hazard ratio for disease recurrence. CONCLUSIONS: The results show that the presence of occult tumour cells in peritoneal lavage is a negative prognostic factor for survival in pancreatic cancer patients, and that detection of occult tumour cells using PCR-based methods can identify patients with advanced disease for whom radical surgery is likely to have little benefit.
Keywords: Disease-Free Survival; ascitická tekutina; karcinoembryonální antigen; Ascitic Fluid; Male; telomerasa; lokální recidiva nádoru; prognóza; Carcinoembryonic Antigen; Adult; Aged; dospělí; mužské pohlaví; senioři; Pancreatic Neoplasms; Neoplasm Recurrence, Local; senioři nad 80 let; lidé; Telomerase; ženské pohlaví; Biomarkers, Tumor; adenokarcinom; Humans; nádory slinivky břišní; erbB receptory; Aged, 80 and over; Prognosis; Adenocarcinoma; Female; ErbB Receptors; lidé středního věku; nádorové biomarkery; přežití bez známek nemoci; Middle Aged